Evaluación de la gestión y calidad del servicio que brinda el centro de salud Carlos Morales Locke de Junín - Andrade Andrade, Yuri Sebastián (2018)
The management and quality evaluation of the service at the Carlos Morales Locke health center, had the purpose of assessing the management of the resources and knowing the perceptions and expectations of the users - patients, for this, in the first instance an interview with the director of the institution was carried out, which allowed to identify the processes that are developed within each area; later, the management of resources was evaluated, where it could be perceived that the economic resource is not enough to meet the current demand. Consecutively, a field study was carried out through the SERVQUAL matrix, managing to be aware of the degree of satisfaction of the users, focusing on the dimensions: tangible elements, reliability, empathy, responsiveness and security. These results were represented in statistical graphs for a better understanding, which helped to recognize the limited management in relation to the technological aspect and infrastructure, both physical and materials. Finally, strategies were designed to the problems encountered to improve them, which in their context have specific objectives, necessary resources, established times, immersed personnel, among others; all in order to provide a better service to users.